Spatial Modeling of Flood Sea Tides (Case Study: East Coast Semarang) - Muhammad Aris Marfai (Universitas Muhammadiyah Surakarta, 2004)
The aims of this research are 1) to construct a spatial model of tidal flood hazard, 2) to do hazard analysis of tidal flood. Spatial modelling has been generated using Geographic Information System (GIS) software and ILWIS software was seleccted to do the model operation. Neighborhood function and digital elevation model (DEM) have been applied on the modelling calculation process. DEM data was correted and menipulated using map calculation on the digital form. Tidal flood hazard analysis has been done by means of map calulation on the tidal flood hazard map and detail landuse map. Histogram and tabulation from the result of the map calculation have been analyzed to identify the impact of the tidal flood hazard on the landuse. The highest impact of the tidal flood hazard occurs on the 1 meter of tidal flood level, where in the inundation occurs mainly on the fishpond and yard/ open space area.